Predictors of Central Line Associated Blood Stream Infections (CLABSI) among patients admitted in Intensive Care Unit of a teaching hospital - Ghimire, Ramesh; Gaudel, Ashim (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Central venous catheters (CVCs) are commonly used in critically ill patients for various indications, including hemodynamic monitoring, administration of medications, and other therapeutic interventions. Central Line Associated Blood Stream Infections (CLABSI) are serious complications of CVCs, leading to increased morbidity, mortality, and healthcare costs due to immunosuppression, prolonged catheter use, and frequent access. The study was designed to explore the predictors of CLABSI among patients admitted in intensive care units (ICU).Methods: A prospective, observational study was conducted among 112 patients with CVCs from February 2023 to January 2024, recruited through consecutive sampling, using a structured proforma. The data was analyzed using descriptive and inferential statistics.Results: A total of nine episodes in 112 patients succumbed an incidence of CLABSI of approximately 8.03%, with a rate of 10.05 per 1,000 catheter days. Age, site of port, number of catheter days, and associated co-morbidities were significantly associated with the incidence, at the level of p-value